TRANSMISI NIRKABEL SINYAL AUSKULTASI SUARA JANTUNG DENGAN MENGGUNAKAN WIRELESS ZIGBEE NETWORK - Oktarina, Eka Sari; Jusak, Jusak; Puspasari, Ira (Journal of Control and Network Systems, 2015)
Heart disease can attack anyone at anytime. Sometimes itâs appearance cannot be dettected early. Heart examination processesthat are done by doctorscommonly called as auscultation. The auscultation is a Â performance examination organs like heart by listening voice resulted from vibration of stetoscope. Furthermore, phisical examination using the stetoscope are mostly required the patients to open their chest area. For that reason, it is necessary to built a tool that is able to seperate the doctor dan the patients.Â Â Â Â Â Â Â Â In this study, a heart sound signal auscultation through wireless transmision in the wireless sensor network is built. Quality of service that are employed in this study including probality of loss, the amount of delay of the received dataas well as the amount of heart auscultation signal bandwidth that are transmited between two nodes.Based on the result, it shows that the higher the baudrate of data delivery set by the serial communication, the larger the throughput of the system. However, it directly affects the packet loss in a way that the packet loss becomes larger. On the other hand, in terms of delay our study shows that large baudrate produces large delay data transmission.Â Keywords : Sinyal Auskultasi Jantung, Wireless Sensor Network, Zigbee